KAJIAN KINERJA BETON RAMAH LINGKUNGAN DENGAN PEMANFAATAN SERBUK CANGKANG TELUR SEBAGAI PENGGANTI SEBAGIAN SEMEN - Fas'ul Akbar; Irene Tresna Wiati; Farah Mawaddah (Racic : Rab Construction Research, 2026)
This study aims to analyze the effect of using Eggshell Powder (ESP) as a partial cement replacement on the fresh properties and compressive strength of mortar. The mixtures consisted of a control mortar (S100), mortar with 10% ESP replacement (S90C10), and mortar with 20% ESP replacement (S80C20). The tests conducted included material characterization using X-Ray Diffraction (XRD) and X-Ray Fluorescence (XRF), Flow Table Test, Vicat Needle Test, and compressive strength tests at curing ages of 3, 7, and 28 days. The XRD and XRF results indicated that eggshell powder was predominantly composed of calcium carbonate (CaCO₃) in the form of calcite. The Flow Table Test results showed that the addition of ESP reduced the flowability of the mortar. The Vicat Needle Test demonstrated that increasing ESP content prolonged both the initial and final setting times. In terms of compressive strength, the S90C10 mixture achieved the highest value at 28 days, reaching 36.80 MPa, which was higher than the control mortar at 34.40 MPa. The results indicate that a 10% ESP replacement level is the optimum proportion, as it enhances mortar compressive strength despite reducing workability and increasing setting time